Biodegradable Spoon Based on Glycerol and Cassava Starch with The Addition of Sugar Cane Pulp - Andrew Setiawan Rusdianto; Winda Amilia; Ade Liya Pratiwi; Hifdzil Adila (International Journal on Food, Agriculture and Natural Resources, 2023)
Biodegradable Spoon is an environmentally friendly spoon-based product made from cassava starch, glycerol, and sugarcane. The research aims to determine the influence of the addition of sugar cane to biodegradable spoon characteristics. This research uses a completely randomized design (RAL) with 1 factor that is the variation of the addition of sugarcane. Each treatment is 3 times repeated and 2 observations. The results showed that the addition of sugarcane affects the value of water content, solubility as well as biodegradability of the spoon. The moisture content of ingredients ranges between 3.78-2.16%. The time of solubility in biodegradable spoon water is increasing with the highest time being 79 hours 50 minutes. The value of biodegradability of the highest spoon in the treatment of adding a 0% cane pulp with a value of weight loss of 52.92%, but on the other hand the increase of sugarcane is added the value of biodegradation increased.